(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The corporate image, or reputation, shows the way in which a company, its exercises, its products or its administrations are seen as untouchable. In an aggressive business atmosphere, many organizations work effectively to create and convey a positive image to their clients, investors, the financial community and the general public. The corporate image is how the company is seen in the eyes of its customers, employees, investors and the general public. A corporate image is important identity of the company wants to project and which will help achieve its objectives. In today’s competitive world, corporate image is an essential component that impacts corporate reputation that eventually impacts customer loyalty. All these are very essential to make a brand successful. “The most critical, strategic and perhaps enduring asset that a corporation possesses is its reputation”. Having a good image is not enough today. One has to have an image which is not only good but much better than its competitors. Also, a continuous effort has to be made to maintain and enhance a company’s image. In this article, we studied various mediums like Public Relations and Advertising for maintaining Corporate Image of a Firm.